Parameter study of a 5G array antenna at 28 GHz - Asma Lak (Scientific Reports)
Abstract In this paper a 5G compact antenna is investigated at 28 GHz. The structure is based on Quasi-Yagi antenna comprising a director, driver, and reflector. The SIW technology is utilized to feed the antenna because of its numerous benefits. The antenna array is designed and simulated and the S11, E pattern, and H pattern are analyzed for both single-element and array antennas. Moreover, the effects of various parameters such as the number of stubs, the length of the director, the distance between the director and driver, the length of the driver, and the distance between the driver and reflector on S11 are studied. The HFSS and CST software are used for all analyses. Additionally, for the array antenna the effects of increasing the number of directors on S11 and antenna gain, change in antenna length, and variations in distances between elements are evaluated.